Single dose pharmacokinetics of oral tenofovir in plasma, peripheral blood mononuclear cells, colonic tissue, and vaginal tissue - Louissaint, Nicolette A; Cao, Ying-Jun; Skipper, Paul L; Liberman, Rosa G; Tannenbaum, Steven R; Nimmagadda, Sridhar; Anderson, Jean R; Everts, Stephanie; Bakshi, Rahul; Fuchs, Edward J; Hendrix, Craig W (AIDS research and human retroviruses, 2013)
HIV seroconversion outcomes in preexposure prophylaxis (PrEP) trials of oral tenofovir (TFV)-containing regimens are highly sensitive to drug concentration, yet less-than-daily dosing regimens are under study. Description of TFV and its active moiety, TFV diphosphate (TFV-DP), in blood, vaginal tissue, and colon tissue may guide the design and interpretation of PrEP clinical trials. Six healthy women were administered a single oral dose of 300 mg tenofovir disoproxil fumarate (TDF) and 4.3 mg (12.31 MBq, 333 μCi) (14)C-TDF slurry. Blood was collected every 4 h for the first 24 h, then at 4, 8, 11, and 15 days postdosing. Colonic and vaginal samples (tissue, total and CD4(+) cells, luminal fluid and cells) were collected 1, 8 and 15 days postdose. Samples were analyzed for TFV and TFV-DP. Plasma TFV demonstrated triphasic decay with terminal elimination half-life median [interquartile range (IQR)] 69 h (58-77). Peripheral blood mononuclear cell (PBMC) TFV-DP demonstrated biphasic peaks (median 12 h and 96 h) followed by a terminal 48 h (38-76) half-life; Cmax was 20 fmol/million cells (2-63). One day postdose, the TFV-DP paired colon:vaginal tissue concentration ratio was 1 or greater in all subjects' tissue homogenates, median 124 (range 1-281), but was not sustained. The ratio was lower and more variable in cells extracted from tissue. Among all sample types, TFV and TFV-DP half-life ranged from 23 to 139 h. PBMC TFV-DP rose slowly in the hours after dosing indicating that success with exposure-driven dosing regimens may be sensitive to timing of the dose prior to exposure. Colonic tissue homogenate TFV-DP concentrations were greater than in vaginal homogenate at 24 h, but not in cells extracted from tissue. These and the other pharmacokinetic findings will guide the interpretation and design of future PrEP trials.